Bioengineering ethics for the age of microphysiological systems - Gaillard, Maxence (Frontiers in Bioengineering and Biotechnology, 2025)
The development of microphysiological systems (MPS) is pushing ethical standards in biomedical research to a breaking point. This article argues that only a perspective drawing from engineering ethics will be able to address the new challenges raised by organoids and organs-on-chips. Extending progressively the scope of moral questioning, we discuss successively the following areas: i) individual consent: when cell lines are generated and human biomaterial is circulated and incorporated into biotechnologies whose life cycle will far exceed the scope envisioned by donors and manufacturers, the classic notion of informed consent becomes almost obsolete, or at least needs to be revisited. ii) Collective deliberation: MPSs raise many expectations for animal replacement and the advancement of precision and regenerative medicine. The management of these prospects by different stakeholders, and for everyone, is itself an ethical challenge at the interface of science and society. iii) Consideration of novel entities: some complex microphysiological systems may be endowed with a moral status in the near future, and this will have an impact on how researchers treat them and work with them.